Designing a building based on a zero-carbon architectural approach in Khorramabad city - niloufar azizifard; salahodin molanai (مهندسی و مدیریت ساخت)
Todey ,the whole world is involved with the energy crisis therefore renewable resources should be repl aced by non-renewable resources with proper principles and planning. one of the important solutions to use the design of buildings based on zero energy.The aim of this thesis is to design a building based on a zero-carbon architectural approach in Khorramabad city.The research method is descriptive-survey. The statistical population in the qualitative section was 12 people interviewed. In the quantitative section, 136 people were selected as a random stratified statistical sample. The analysis was performed using RISREL version 22 software.The results of the interview with experts using the Delphi method led to the identification of 11 main indicators, namely (appropriate construction design, energy optimization, attention to environmental considerations, appropriate use of building materials, optimization of construction costs, beauty of the building facade, attention to climatic conditions, building orientation, heat storage method, energy consumption, arrangement of rooms in the building).The research findings showed that the indicators extracted for designing a building based on a zero-carbon architectural approach have a significant relationship with each other directly and indirectly at the 99% level.The simulation results showed that by using zero carbon indicators in the building identified by experts, energy consumption can be reduced optimally.